Preliminary Phytochemical Screening and Antioxidant Activity of Commercial Moringa oleifera Food Supplements - Eulogio J. Llorent-Martínez; Ana I. Gordo-Moreno; María Luisa Fernández-de Córdova; Antonio Ruiz-Medina (MDPI AG, 2023)
Moringa oleifera has been reported to possess a high number of bioactive compounds; hence, several food supplements are commercially available based on it. This work aimed to analyze the phytochemical composition and antioxidant activity of commercial food supplements. The phenolic composition of methanolic extracts was determined by using high-performance liquid chromatography with diode-array and electrospray ionization mass spectrometric detection (HPLC-DAD-ESI-MSn), and the antioxidant activity was assessed by ABTS·+ and DPPH assays. Thirty-three compounds were identified, and all the main compounds were quantified, observing that the main contribution to the phenolic profile was due to kaempferol and quercetin glucosides. The antioxidant activity in both assays agreed with the phenolic content: the higher the phenolic levels, the higher the antioxidant activity. The obtained results were compared with those previously published regarding Moringa oleifera leaves to establish the potential benefits of food supplement consumption in the diet.